Process of EUR prediction for shale gas wells based on production decline models—a case study on the Changning block - Liu, Sha; Chang, Cheng; Xie, Weiyang; Li, Hong (Frontiers in Energy Research, 2023)
To effectively develop the shale gas in the southern Sichuan Basin, it is essential to accurately predict and evaluate the single-well production and estimated ultimate recovery (EUR). Empirical production decline analysis is most widely used in predicting EUR, since it is simple and can quickly predict the gas well production. However, this method has some disadvantages, such as many parameters of the model, difficulty in fitting and large deviation. This paper presents an efficient process of EUR prediction for gas wells based on production decline models. Application of nine empirical production decline models in more than 200 shale gas wells in the Changning block of the Sichuan Basin was systemically analyzed. According to the diagnosis of flow regime, it was determined that all models are applicable in the prediction of production and EUR in this area, with the fitting degree higher than 80% for gas wells producing for more than 12 months. Based on the fitting and prediction results, the parameter distribution charts of the nine production decline models with initial parameters constrained were plotted for shale gas wells, which greatly improved the prediction accuracy and efficiency. Coupled with the probability method, the EUR was evaluated and predicted effectively, and the average EUR of more than 200 shale gas wells in the Changning block is 1.21 × 108 m3. The EUR of Well CNH1 predicted by the proposed process and charts is believed reliable. The study results provide meaningful guidance for the efficient prediction of gas well production and EUR in the Changning block.